THE EFFECT OF SELF-EFFICACY AND RELIGIOSITY ON ACADEMIC CHEATING - Dinda Fauzi Siregar; Salamiah Sari Dewi; Ummu Khuzaimah (RADJA PUBLIKA, 2025)
This study examined the predictive roles of self-efficacy and religiosity on academic cheating among students at University X in Medan City. Employing a quantitative research design, this study collected data from 195 student participants. The tendency for academic cheating, along with levels of self-efficacy and religiosity, were measured using established scales.The results revealed that self-efficacy was a significant negative predictor of academic cheating. Higher levels of self-efficacy were strongly associated with a lower propensity for such misconduct, highlighting that a student's confidence in their own academic abilities serves as a key protective factor. Similarly, religiosity was found to have a significant negative relationship with academic cheating. Students reporting higher levels of religiosity, guided by strong moral and ethical values, were less inclined to engage in dishonest academic practices. Furthermore, the analysis identified a significant joint effect, where the combination of high self-efficacy and high religiosity provided the strongest deterrent against academic cheating. These findings underscore that both internal psychological confidence and a strong moral framework derived from religiosity are crucial in fostering academic integrity, making students who possess both traits most likely to act with honesty and responsibility.